PENGAWASAN MAHASISWA BIDIKMISI DI UNIVERSITAS NEGERI PADANG - sri okto berta; Dasman Dasman; Adil Mubarak (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2019)
In the implementation of the Bidikmisi program there are various problems that are not in accordance with the 3T principles, namely Timely, Right Amount and Right Target so that supervision is needed, supervision is carried out to monitor, foster and resolve problems that may arise from the policy. This study discusses Supervision of Bidikmisi students in the form of preventive and repressive at Padang State University. The purpose of this study is to describe the supervision of Bidikmisi students, obstacles and efforts to minimize the obstacles in supervising Bidikmisi students at Padang State University. This type of research is qualitative research with descriptive analysis methods. The research location is at Padang State University. Primary data is data obtained from interviews and observations, while secondary data is data obtained from documentation studies. The informants in this study were the Head of BAK UNP, UNP Student Affairs Department, Deputy Dean III FIS, FT and FBS, and several Bidikmisi recipient students. Based on the results of the research carried out it can be concluded as follows: First, the supervision carried out by UNP in supervising the Bidikmisi students at UNP is good but not optimal, this is proven by the fact that UNP is conducting monitoring, both preventive and repressive, but there are still students Bidikmisi who do not participate. Preventive in the form of socialization, training and repressive in the form of guidance and even the termination of the tuition assistance for Bidikmisi. Second, the obstacle faced by Padang State University is an internal obstacle, namely the lack of a survey team that creates opportunities for Bidikmisi target inaccuracies and other obstacles, namely from Bidikmisi students themselves, about the commitment and seriousness of Bidikmisi students in fulfilling their duties and responsibilities as Bidikmisi students. Third, efforts made to overcome these obstacles are by optimizing coaching through socialization, training and guidance for Bidikmisi candidates and students.